2013
DOI: 10.1371/journal.pone.0071638
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community-Based Larviciding on the Prevalence of Malaria Infection in Dar es Salaam, Tanzania

Abstract: BackgroundThe use of larval source management is not prioritized by contemporary malaria control programs in sub-Saharan Africa despite historical success. Larviciding, in particular, could be effective in urban areas where transmission is focal and accessibility to Anopheles breeding habitats is generally easier than in rural settings. The objective of this study is to assess the effectiveness of a community-based microbial larviciding intervention to reduce the prevalence of malaria infection in Dar es Salaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(155 citation statements)
references
References 49 publications
(63 reference statements)
6
147
2
Order By: Relevance
“…Documentation of these benefits may be of interest to contemporary antimalaria programs seeking to avoid negative consequences of large-scale outdoor pesticide spraying (Fillinger and Lindsay, 2011;Gu et al, 2008;Keiser et al, 2005;Maheu-Giroux and Castro, 2013;Nájera et al, 2011;WHO, 2012). 26…”
Section: Evidence For a Valid Pre-treatment Period And Treatment Onsetmentioning
confidence: 99%
“…Documentation of these benefits may be of interest to contemporary antimalaria programs seeking to avoid negative consequences of large-scale outdoor pesticide spraying (Fillinger and Lindsay, 2011;Gu et al, 2008;Keiser et al, 2005;Maheu-Giroux and Castro, 2013;Nájera et al, 2011;WHO, 2012). 26…”
Section: Evidence For a Valid Pre-treatment Period And Treatment Onsetmentioning
confidence: 99%
“…Biological larvicides such as Bacillus thuringiensis israelensis (Bti) are environmentally safe, target species specific in their mode of action, and show no resistances 12 . Within the last decade there has been a large body of evidence generated, showing that Bti based larviciding can bring down malaria vector populations by order of magnitude and significantly reduce malaria prevalence [13][14][15][16] . Recommendations from the WHO currently limit the use of larviciding to urban environments due to the high population density, which provides lower per capita intervention costs compared to less densely populated areas 4 .…”
mentioning
confidence: 99%
“…A different cross-sectional formulation, accounting for follow-up data, considering time trend modeled as a first-order autoregressive process, and modeling rainfall with a smooth function where the spline penalty follows a second-order random walk process indicated that the odds of individuals living in areas treated with larviciding being infected with malaria were 21% lower than those who lived in areas not treated; the reduction in the odds was 40% in the dry season. 3 …”
Section: Discussionmentioning
confidence: 99%
“…2 We chose the UMCP because the program collected both longitudinal and cross-sectional data, with more than 64,000 observations gathered for more than 4 years. Previous evaluations have shown that the intervention significantly reduced the prevalence of malaria infection in intervention areas, 3,4 although none comprehensively addressed the methodological challenges of analyzing a complex dataset such as the UMCP.…”
Section: Introductionmentioning
confidence: 99%